Pollinator responses to farmland habitat features: one-size does not fit all - Maher, Stephanie; Kelly, Ruth; Hodge, Simon; O'Hora, Ellen; Ruas, Sara; Rotches-Ribalta, Roser; Lee, Alan; White, Blanaid; Gormally, Mike; Moran, James; Ó hUallacháin, Daire; Stout, Jane (Journal of Pollination Ecology, 2024)
Globally, pollinating insects face significant pressure, largely due to intensively managed agricultural systems. There has been considerable focus on the provision of resources for pollinators in agricultural landscapes, but without understanding how existing farmland habitats affect pollinators there is a risk these conservation actions could fail. The aim of this study was to explore the relationships between the quantity, diversity, and quality of on-farm habitats with pollinator communities. To meet this aim, pollinator, floral and habitat features were assessed at twenty-nine sites, encompassing both livestock and crop systems, at a range of farming intensities, in two regions of Ireland. Results showed that the three main taxonomic pollinator groups (hoverflies, social bees, and solitary bees) were inconsistent in their responses to habitat and environmental variables. Hoverflies were negatively associated with farms with increasing amounts of linear feature and fewer drainage ditches, whereas bumblebees were positively associated with crop farms and the number of grassy margins, drainage ditches and hedgerows at a site. Solitary bees were negatively associated with crop farms and positively associated with high floral species richness. At a species level, community analysis showed that within taxonomic groups, individual species responded differently to environmental variables. This study demonstrates that different farm types and habitat features impact pollinator groups differently. One-size does not fit all, thus on-farm conservation actions should be designed with knowledge of taxon-specific responses to maximise benefits. The quantity and diversity of essential habitats are important along with the quality of those features in terms of their capacity to provide sufficient resources for pollinators.